2015
DOI: 10.1118/1.4921363
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prone versus supine 18F‐FDG‐PET of locally advanced breast cancer: Phantom and preliminary clinical studies

Abstract: Purpose: Previous studies have demonstrated how imaging of the breast with patients lying prone using a supportive positioning device markedly facilitates longitudinal and/or multimodal image registration. In this contribution, the authors' primary objective was to determine if there are differences in the standardized uptake value (SUV) derived from [ 18 F]fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) in breast tumors imaged in the standard supine position and in the prone position using a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In this study, we quantitatively evaluated TOF-reconstructed PET/CT images, since edge artefacts are known to occur in PSF modelling during reconstruction and are significant for small lesions [ 33 ]. Furthermore, some reports have shown that visualisation of small breast lesions can be improved by performing PET/CT in the prone position using assistive devices to allow breast expansion and suppression of respiratory movements [ 34 , 35 ]. PET technologies, such as TOF and PSF, smaller pixel sizes, and prone position scanning, are expected to improve the visual detection rate of smaller lesions using PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we quantitatively evaluated TOF-reconstructed PET/CT images, since edge artefacts are known to occur in PSF modelling during reconstruction and are significant for small lesions [ 33 ]. Furthermore, some reports have shown that visualisation of small breast lesions can be improved by performing PET/CT in the prone position using assistive devices to allow breast expansion and suppression of respiratory movements [ 34 , 35 ]. PET technologies, such as TOF and PSF, smaller pixel sizes, and prone position scanning, are expected to improve the visual detection rate of smaller lesions using PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we quantitatively evaluated TOF-reconstructed PET/CT images, since edge artefacts are known to occur in PSF reconstruction and are signi cant for small lesions [30]. Furthermore, some reports have shown that visualisation of small breast lesions can be improved by performing PET/CT in the prone position using assistive devices to allow breast expansion and suppression of respiratory movements [31,32]. PET technologies, such as TOF and PSF, smaller pixel sizes, and prone position scanning, are expected to improve the visual detection rate of smaller lesions using PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Sensors operated in 2-second cycles: 1 second to count the activity followed by 1 second to record the data. Near the end of the uptake period (42 – 59 min post-FDG) sensors were removed, and patients underwent limited whole-body PET/CT (i.e., top-of-skull to mid-thigh FOV) in a Discovery STE scanner (GE Healthcare, Waukesha, WI, USA) as previously described [10]. …”
Section: Methodsmentioning
confidence: 99%